Night flight : Amelia Earhart crosses the Atlantic - Burleigh, Robert (Simon & Schuster Books for Young Readers, 2011)
An account of Amelia Earhart's dangerous 1932 flight across the Atlantic Ocean from Newfoundland to Ireland, in which she survived bad weather and a malfunctioning airplane. Includes a brief biography of the aviator.